Synthesis of Shielding Radiation Neutron Materials Made from Wood Powder With Variation of Borax Content - Rohmad Salam; Agus Salim Afrozi (Jurnal Ilmiah Teknik Kimia, 2021)
Synthesis of Shielding Radiation Neutron Materials Made from Wood Powder with Variation of Borax Content has been carried out as a shield of neutron radiation. The material used as a neutron shield is wood powder added 10%, 20%, 30% and 50% borax with variations in the thickness of each 5 mm, 10 mm, 15 mm, which previously saw wood powder milled with HEM (High Energy Milling ) for 1 hour and mixed with borax using HEM (High Energy Milling) for 1 hour and compacted using a diameter of 25.4 mm with a pressure of 2000 Psi. The results of observations with optical microscopes show that the spread of borax which is less evenly distributed may be due to the type of borax that is used in wood blends that have properties that quickly clot and cannot be evenly mixed with wood. The results of the compressive test using a Universal Tensile Machine tool produced strong for 224 N wood and in the mixture of 50% borax wood which was closest to the strength of wood which was equal to 172 N